(untitled) (Ciencias de la Ingeniería y Aplicadas, 2026)
The problem investigated arose from the identification of persistent deficiencies in doctoral theses, master’s degrees and diploma theses related to hypothesis validation. The objective of this work was determined to show how to validate a hypothesis by using the non-parametric statistical test: Sign Test for a small sample, which allows to determine, with a certain level of confidence, if the results of: a new methodology, strategy, technology, treatment, among others, applied to the same sample: group of people, objects or processes were superior to an initial state with respect to the sample taken as the object of study. The doctoral thesis by Espinosa (2012) was taken as a reference, in which the Work Performance of the intentional sample taken from Middle Technicians in Industrial Mechanics was compared before (February 2011) and after applying the proposed Methodology, which made it possible to validate, with a greater degree of confidence, the research object of study.